PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK PENINGKATAN KEMAMPUAN BERPIKIR KREATIF DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK - Marda Novellia (Journal for Lesson and Learning Studies, 2018)
This research is a Classroom Action Research (PTK) which aims to improve the ability of creative thinking and student learning outcomes fourth grade SD Negeri Mangunsari 03 Salatiga. Problems encountered in the learning process include students tend to be less active, monotonous learning, most students tend not to ask questions and some students' creative thinking ability is still not seen. To overcome these problems, the researcher conducted a class action research related to the application of Problem Based Learning (PBL) learning model to improve creative creativity and learning result of fourth grade students of SD Negeri Mangunsari 03 Salatiga on Theme 7 Subtema 2 and 3 semesters II. The study consists of two cycles, each cycle consisting of three meetings each consisting of action planning, action execution, observation, and reflection and evaluation. The data in this research is obtained from observation, document study, and test. Improvement of students 'creative thinking ability can be shown pre-cycle percentage of students' creative thinking ability 71,06% then increase in cycle I with percentage 86,84% again increase in cycle II with percentage 89,47%. While the result of student learning in pre cycle with percentage 55,26% increase in cycle I with percentage 78,94% and in cycle II again increase with percentage 86,84%. Thus, with the application of Problem Based Learning (PBL) model proved able to improve the ability of creative thinking and learning outcomes of fourth grade students of SD Negeri Mangunsari 03 Salatiga in Theme 7 Subtema 2 and 3.